Eksistensi Tradisi Lukat Geni Di Desa Paksebali Kecamatan Dawan Kabupaten Klungkung - Desak Made Ayu Indri Safira; Gede Mahardika; I Made Hartaka (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
A culture will certainly still exist if it still has an influence on human life. In Paksebali Village there is a tradition that still exists and has been carried out since the past until now. The tradition is the Lukat Geni tradition. Tradition is a tradition or custom that is passed down from generation to generation and is carried out repeatedly. According to the Big Indonesian Dictionary, tradition is everything such as customs, habits, teachings and so on that have been passed down from generation to generation from ancestors. Tradition comes from the word traditium which means everything that is transmitted, passed down from the past to the present. The point is that tradition is a legacy from the past that is preserved and carried out in the present. Bali has many traditions, almost all areas in Bali have unique traditions and run them according to the culture and customs of each region. For example, the Lukat Geni tradition is held in Paksebali Village, Dawan District, Klungkung. The Lukat Geni tradition is a sacred tradition that is believed by the community to have a positive impact on the lives of the local community. Therefore, this tradition can be said to exist until today.